2019
DOI: 10.1590/1516-4446-2018-0183
|View full text |Cite
|
Sign up to set email alerts
|

From anatomy to function: the role of the somatosensory cortex in emotional regulation

Abstract: Since the pioneering work of Penfield and his colleagues in the 1930s, the somatosensory cortex, which is located on the postcentral gyrus, has been known for its central role in processing sensory information from various parts of the body. More recently, a converging body of literature has shown that the somatosensory cortex also plays an important role in each stage of emotional processing, including identification of emotional significance in a stimulus, generation of emotional states, and regulation of em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
161
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(196 citation statements)
references
References 57 publications
(224 reference statements)
8
161
2
2
Order By: Relevance
“…(3) Leptin mediated both the association between ReHo alterations (primary somatosensory and visual association cortices) and core depressive symptoms as well as BMI. These findings are consistent with an expanding literature implicating primary somatosensory cortex 5,38,39 , visual association cortex 40,41 and leptin 25,42 in depression and further suggesting that depressive symptoms are dimensional features across MPDs. Utilising a transdiagnostic approach, the extent of overlap and distinct alterations in ReHo values among SCZ, BPD and MDD were examined.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…(3) Leptin mediated both the association between ReHo alterations (primary somatosensory and visual association cortices) and core depressive symptoms as well as BMI. These findings are consistent with an expanding literature implicating primary somatosensory cortex 5,38,39 , visual association cortex 40,41 and leptin 25,42 in depression and further suggesting that depressive symptoms are dimensional features across MPDs. Utilising a transdiagnostic approach, the extent of overlap and distinct alterations in ReHo values among SCZ, BPD and MDD were examined.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with a previous study 18 , we observed ReHo alterations in primary sensory, visual association and orbital frontal cortices associated with depressive symptoms. The abovementioned brain regions are involved in emotion processing [38][39][40]47 . Primary somatosensory and visual association cortices play important roles in encoding somatosensory sensations and emotional recognition and regulation 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Component-1 showed a ventral-to dorsal gene expression pattern that was associated with higher correlations between CT and clinical scores, namely, the mental state of Parkinson's disease patients and the performance of motor functions. The pathways involved in ER-Golgi traffic were notably high expressed in the postcentral gyrus which contains the somatosensory cortex that is known for its role in processing sensory information and the regulation of emotion (Kropf et al, 2019). Our results suggest that genes in ER-Golgi traffic pathways are important for cognitive functions controlled by the postcentral gyrus.…”
Section: Discussionmentioning
confidence: 58%
“…In particular, the SI participates in processing emotional significance, emotion regulation and in the generation of the emotion of fear (71).…”
Section: Discussionmentioning
confidence: 99%